Food intake and digestive efficiency in temperate wool and tropic semi-arid hair lambs fed different concentrate: forage ratio diets - Silva, AMA; Sobrinho, AGS; Trindade, IACM; Resende, Kleber Tomás de [UNESP]; Bakke, O. A. (Elsevier B.V., 2004)
This work was conducted to evaluate food intake and digestive efficiency of temperate wool and tropic semi-arid hair lambs, according to different concentrate: forage ratios in diet. Twenty-four lambs, averaging 90 +/- 1.8 days old and a mean body weight of 20 +/- 0.69 kg, 12 of them wool lambs, F, from Ideal x Ile de France crossing, and 12 others pure Santa Ines hair lambs, were distributed into a four replication 3 x 2 factorial arrangement consisting of three diets and two genotypes. Experimental diets consisted of: D1 = 60% concentrate mix (C) and 40% Cynodon sp. cv. Tifton-85 hay (F), D2 = 40% C and 60% F, and D3 = 20% C and 80% F. D1 was formulated for a daily gain of 300g per animal. Increasing forage levels in diets resulted in linear reductions (P < 0.01) in DM, OM, CP, TCH and metabolizable energy (ME) intake, and a linear increase (P < 0.01) in NDF ingestion. Tropic semi-arid hair lambs had higher DM, OM, NDF, CP, and TCH intake than temperate wool lambs. Although there were no genotype effects in OM and GE coefficient of digestibility, hair lambs showed more efficient (P < 0.05) digestibility of DM, CP, NDF and TCH. Increases in forage levels of diets corresponded to a negative linear effect (P < 0.01) in the apparent digestibility of DM, OM, CP, TCH and GE, while apparent digestibility of NDF increased linearly (P < 0.01). Total endogenous nitrogen (fecal plus urinary N) for F(1) Ideal x Ilede France wool and Santa Ines hair lambs were, respectively, 182 and 312 mg/kg(0.75) per day. Thus, Santa Ines tropic semi-arid hair lambs showed to be more responsive than F(1) Ideal x Ile de France temperate wool lambs to low quality fibrous diets. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: lamb; neutral detergent fiber; roughage fodder; intake; Digestibility; Tifton